High Health-Related Quality of Life During Dendritic Cell Vaccination Therapy in Patients With Castration-Resistant Prostate Cancer - Westdorp, Harm; Creemers, Jeroen H. A.; van Oort, Inge M.; Mehra, Niven; Hins-de Bree, Simone M.; Figdor, Carl G.; Witjes, J. Alfred; Schreibelt, Gerty; de Vries, I. Jolanda M.; Gerritsen, Winald R.; Ottevanger, Petronella B. (Frontiers in Oncology, 2020)
Background Maintaining health-related quality of life (HRQoL) is highly desirable during systemic therapies for patients with castration-resistant prostate cancer (CRPC). Patient-reported outcome measures (PROs) were studied in our phase IIa trial on cellular-based immunotherapy with dendritic cells (DC). Methods We treated 21 chemo-naive asymptomatic or minimally symptomatic patients with CRPC with maximally three cycles of DC vaccinations (ClinicalTrials.gov, NCT02692976). Here, we report the impact of DC vaccination on HRQoL. PROs were assessed using the EORTC-QLQ-C30, the EORTC-QLQ-PR25, Checklist Individual Strength (CIS20-R), and Beck Depression Inventory Primary Care questionnaires. Short-term and long-term vaccine-related effects on HRQoL were studied. Results Questionnaires were collected at baseline (n=20), week 6 (n=19), week 12 (n=18), week 24 (n=13), week 50 (n=8) and week 100 (n=2). No clinically relevant differences in symptom-related outcome, functioning-related outcome, and Global Health Status were observed directly after the first cycle of DC vaccinations (week 6) and at follow-up (week 12) compared to baseline. HRQoL remained high throughout the vaccination cycle and six weeks afterward. In radiographic non-progressive patients, who continued DC vaccination, high HRQoL scores were observed up to one and two years after study enrolment. Conclusions Patients with asymptomatic or minimally symptomatic CRPC show high HRQoL throughout DC-based immunotherapy. This is a clinically relevant finding in this older-aged patient population with advanced prostate cancer.